2023
DOI: 10.3389/fcimb.2023.1122059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, multiple antibiotic resistance and virulence profile of methicillin-resistant Staphylococcus aureus (MRSA) in retail poultry meat from Edo, Nigeria

Abstract: IntroductionStaphylococcus aureus causes staphylococcal food poisoning and several difficult-to-treat infections. The occurrence and dissemination of methicillin-resistance S. aureus (MRSA) in Nigeria is crucial and well documented in hospitals. However, findings on MRSA from meat in the country are yet to be adequately reported. The current study determined the prevalence, virulence profile and antibiogram characteristics of MRSA from a raw chicken product from retail outlets within Edo.MethodsA total of 368 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The excessive use of antibiotics in livestock, observed in our study area, may be a key driver in the selection of AMR strains. The diverse resistance patterns identified in our research can be attributed to the prolonged and indiscriminate application of various antimicrobial classes in modern agriculture, as highlighted in previous studies 27 , 30 . Bernier-Lachance et al 3 findings, where all isolates exhibited intermediate or full resistance to β-lactams, align with our results.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The excessive use of antibiotics in livestock, observed in our study area, may be a key driver in the selection of AMR strains. The diverse resistance patterns identified in our research can be attributed to the prolonged and indiscriminate application of various antimicrobial classes in modern agriculture, as highlighted in previous studies 27 , 30 . Bernier-Lachance et al 3 findings, where all isolates exhibited intermediate or full resistance to β-lactams, align with our results.…”
Section: Discussionsupporting
confidence: 67%
“…DNA extraction was conducted following a previously established protocol 30 , 49 . To resuscitate all isolates, they were placed in 5 mL of tryptone soy broth after an initial 24-h incubation at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, our findings indicate that S. aureus strains isolated from chicken meat could be a reservoir of resistance and virulence genes. In this regard, in Nigeria, Igbinosa et al [ 65 ] found that of 368 poultry meat samples, 110 (29.9%) were positive for MRSA. Moreover, Ruzauskas et al [ 66 ] reported that 95% of retail raw chicken meat samples in Lithuanian markets were infected with Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread consumption of antibiotics in the livestock sector has led to their persistent release into the environment and increased antibiotic-resistant bacteria. Numerous studies have demonstrated the presence of mec A-positive methicillin-resistant Staphylococcus aureus (MRSA) in various food sources, such as retail meat, fish, poultry, pork, beef, ready-to-eat foods, and even vegetables [ 11 , 19 , 20 , 21 ]. Additionally, CoNS carrying mec A, which are known for their increasing rates of methicillin resistance, have been detected in milk at a rate of 0.6% in Brazil and 6.7% in Tunisia [ 22 , 23 ], in ready-to-eat foods at a rate of 16.4% in Poland [ 24 ], and in meat at a rate 2.3–8% in Egypt [ 25 , 26 ], which raises additional concerns about the spread of resistance.…”
Section: Introductionmentioning
confidence: 99%